Pre‐augmentation soft tissue expansion: an overview. Issue 5 (3rd June 2015) - Asa'ad, Farah; Rasperini, Giulio; Pagni, Giorgio; Rios, Hector F.; Giannì, Aldo B.
Abstract: Objectives: The aim of this study was to explore the development of soft tissue expanders, their different types and their potential applications prior to bone augmentation and implant placement. Material and Methods: A review of pertinent literature was performed using PubMed to comprehend the dynamics of soft tissue expanders and determine the current position of their pre‐augmentation applications. Results: There is promising, albeit preliminary information regarding the benefits of pre‐augmentation soft tissue expansion. Findings cannot be generalised due to relatively small sample size. Conclusions: Further clinical trials with larger sample sizes and long‐term follow‐up are needed before soft tissue expanders can be confidently applied in everyday clinical practice.